PENGARUH CITRA MEREK, PERSEPSI HARGA, DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA AVANZA DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING (Studi pada PT Nasmoco Majapahit Semarang) - Nugraheni, Dyana Putri; Dwiyanto, Bambang Munas (Diponegoro Journal of Management, 2016)
The aim of this study is to analyze the effect of brand image, perceived price, and product attribute on purchase intention and its influence on customer's purchase decision of Toyota Avanza car at PT Toyota Avanza Nasmoco Majapahit Semarang. The variables used in this study are brand image, perceived price, and product attribute as the independent variables, purchase intention as the intervening variable, and purchase decision as the dependent variable.This sample in this study was 132 respondents of PT Nasmoco Majapahit Semarang’s customers who ever used and purchased Toyota Avanza car. The data collecting method used is accidental sampling by distributing questionnaires to the respondents. In this study developed a theoretical model to propose seven hypotheses to be tested using analysis tools Structural Equation Modeling (SEM) which is operated through a program AMOS 20.0.Based on research of data processing SEM for full model has met the criteria of goodness of fit as follows: the value of chi-square = 168,835; probability = 0,062; RMSEA = 0,038; chi-square/df = 1,189; GFI = 0,887; AGFI = 0,848; CFI = 0,993; and TLI = 0,992. Within the result, it could be said that this model is feasible to be used. The result of this study showed that the purchase decision could be improved by increasing product attribute that affects the customer’s purchase intention as a determinant of success increase purchase decision.